2018
DOI: 10.1177/0734242x18806999
|View full text |Cite
|
Sign up to set email alerts
|

Waste of electrical and electronic equipment: Trends and awareness among youths in Lithuania

Abstract: Waste of electrical and electronic equipment (WEEE) has gained significant attention recently because of increasing consumption and related environmental impacts. This work focuses on Lithuania and analyses the trends of WEEE generation and management during the period 2008-2015. Attitudes and behaviour of students and pupils (main future consumers) regarding WEEE are also determined in this work. The analysis shows that the generation and collection of WEEE in Lithuania have been on the rise since the global … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…Furthermore, the consumers' geographical locations impacted waste TV storage behavior, and in that case, the age of the sets was equal or greater than 16 years old. Dagiliūtė et al (2019) indicated that age has a positive association with storage. For example, due to limited purchase power, students tended to use the products as spares.…”
Section: Socio Economic Factorsmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, the consumers' geographical locations impacted waste TV storage behavior, and in that case, the age of the sets was equal or greater than 16 years old. Dagiliūtė et al (2019) indicated that age has a positive association with storage. For example, due to limited purchase power, students tended to use the products as spares.…”
Section: Socio Economic Factorsmentioning
confidence: 99%
“…(2020) mentioned that community-based interventions to improve awareness levels have significance. Dagiliūtė et al (2019) mentioned that despite self-reported awareness, consumers were not familiar with the various classifications of e-waste (category of EEE) under the national EM of Lithuania. Among the various categories of e-waste, SE has a relatively shorter lifespan, and Echegaray (2016) found that the products' expected lifespan decreases with the electronic device's portability.…”
Section: Familiarity Of Collection and Recycling Programsmentioning
confidence: 99%
See 2 more Smart Citations
“…In Lithuania, the survey results highlight that a small amount of WEEE was discarded together with municipal waste. Residents expected more information about WEEE disposal options and more collection points [30]. A study in Portugal identified the sociodemographic factors that influence consumption and recycling behaviors on a case study of tablets and smartphones [31].…”
Section: Introductionmentioning
confidence: 99%